Comparison of Corrosion Hazard Map in 10 Years Duration Using Air Pollution and Climate Data - Izhar A.S.M.; Khalid N.H.N.; Usman F.; Adriyanshah N.F. (Springer Science and Business Media Deutschland GmbH, 2023)
Air pollution; Atmospheric humidity; Decision making; Economics; Geographic information systems; Hazards; Inverse problems; Steel corrosion; Climate data; Common metals; Condition; Corrosion hazard map; Corrosion levels; Hazard map; High humidity; Malaysia; Time of wetness; Tropical climates; Atmospheric corrosion